Caesarean delivery and pubertal timing in boys and girls: A Danish population‐based cohort study. Issue 1 (26th November 2021) - Huang, Kun; Gaml‐Sørensen, Anne; Lunddorf, Lea Lykke Harrits; Ernst, Andreas; Brix, Nis; Olsen, Jørn; Ramlau‐Hansen, Cecilia Høst
Abstract: Background: There is considerable public and scientific interest in the declining age of pubertal timing. Prenatal and postnatal stress has been proposed to relate with earlier pubertal timing, but it remains unknown whether intrapartum stress may affect pubertal timing as well. Objective: This study aims to examine the potential effect of caesarean delivery on pubertal timing in boys and girls. Methods: This study was based upon the nationwide Puberty Cohort nested within the Danish National Birth Cohort (DNBC) from 2000 to 2003. A total of 15, 731 mother‐child pairs with complete information on delivery mode and puberty were included in the main analysis. The delivery mode was categorised into non‐instrumental vaginal delivery (reference), instrumental vaginal delivery, elective caesarean delivery before labour, emergency caesarean delivery during labour and un‐specified caesarean delivery. Children's pubertal development were self‐reported in web‐based questionnaires from 11 years of age and every 6 months throughout puberty (2012–2019), including Tanner stages 2–5, menarche, voice break, first ejaculation, axillary hair growth and the onset of acne. Regression models for censored, normally distributed time‐to‐event data were used to estimate mean monthly differences in age at attaining the different pubertal milestones and the average of all these estimates for each sex (a combined indicator of pubertal timing). Results: A total of 2810 participants were born by caesarean delivery (17.9%). Neither elective nor emergency caesarean delivery was associated with earlier age at achieving the pubertal milestones in boys or in girls. For the combined indicator, the mean age differences for elective caesarean delivery and emergency caesarean delivery were 0.1 (95% CI −1.1, 1.4) months and −0.7 (95% CI −2.0, 0.5) months in boys and 0.7 (95% CI −0.7, 2.0) and 0.2 (95% CI −1.3, 1.7) in girls. Conclusions: This study does not suggest a clinically important effect of caesarean delivery on children's pubertal timing.